The Healthy, Aging, and Diseased Kidney: Relationship with Cardiovascular Disease. Issue 2 (26th October 2020) - Morcos, Ramez; Lazar, Ira; Kucharik, Michael; Lavin, Arye; Fahmy, Andrew; Chandrasekhar, Sanjay; Ibrahim, Amira; Neupane, Aashish; Khalili, Houman; Maini, Brijeshwar; Ouslander, Joseph G.
Abstract : The cardiovascular and renal systems share an intimate physiological relationship, wherein a perturbance in one system may have an adverse effect on the other. Since the burden of renal disease increases with age, there is a considerable interest in the pathophysiology of kidney disease in the geriatric patient population. This review will explore the physiological dynamics behind the increased susceptibility to kidney disease in this population. A better understanding of these pathophysiological changes may lead to improved prevention and management strategies.